Information politics : liberation and exploitation in the digital society - Jordan, Tim, 1959- (Digital barricades., 2015)
Conflict over information is a central part of twenty-first century life. Tim Jordan examines the nature of an information politics that has emergede with the rise of mass digital cultures and the internet. He located it within a field of power and rebellion that is populated by social and political struggles. This book is the ideal place to start for anyone approaching the rapidly changing terrain of digital culture and conflict. -- from back cover.